A family-oriented treatment program for youths with ketamine abuse and their caregivers: a pilot study in Taiwan - Wang LJ (Dove Medical Press, 2015)
Liang-Jen Wang,1 Shing-Fang Lu,1 Wen-Jiun Chou,1 Mian-Yoon Chong,2 Yao-Hsing Wang,1 Yu-Lian Hsieh,1 Yi-Hsuan Lee,1 Ching Chen2 1Department of Child and Adolescent Psychiatry, 2Department of Psychiatry, Kaohsiung Chang Gung Memorial Hospital and Chang Gung University College of Medicine, Kaohsiung, Taiwan Objective: The abuse of ketamine by youths has grown into a serious public health issue. However, a reliable and efficient treatment has still not been found for youths who abuse ketamine. This pilot study investigated the effects of a family-oriented treatment program for ketamine-using youths and their caregivers.Methods: To carry out this study, 42 youths with ketamine use (mean age 16.6±1.1 years) who were referred to take part in a 10-week treatment program based on motivational enhancement principles were selected, as were their principal caregivers (mean age 46.4±7.1 years), who were similarly referred to take part in a 10-week training program for parenting skills. The study had the youths complete the Chinese Craving Beliefs Questionnaire, the Adolescents’ Behavior problem Scale, and the Family APGAR both immediately before and after the program. Likewise, the youths’ caregivers completed the Family APGAR, the 12-item version of the Chinese Health Questionnaire, and the Parenting Stress Index.Results: Of the 42 youth–caregiver pairs that took part in this study, 37 (88%) completed the 10-week program and both sets of assessments. After the treatment, the participating youths’ substance cravings declined (t=3.88, P<0.001), while family function, as perceived by the participating caregivers, significantly increased (t=2.22, P=0.033). The improvement in caregivers’ perceptions of family function were positively related to the improvement of the caregivers’ health status (r=-0.36, P=0.022).Conclusion: According to its results, this pilot study submits that family-oriented treatment programs may be considered a potentially effective treatment option for youths who abuse ketamine. Additional studies with larger sample sizes, as well as longer follow-up periods, are necessary to verify whether this type of treatment also prevents youths using ketamine from relapsing. Keywords: substance abuse, psychotherapy, family, juvenile delinquency